ChemInform Abstract: Aerobic Photooxidative Direct Asymmetric Aldol Reactions of Benzyl Alcohols Using Water as the Solvent. Issue 36 (September 2015) - Fujiya, A.; Nobuta, T.; Yamaguchi, E.; Tada, N.; Miura, T.; Itoh, A.
Abstract Attempted asymmetric aldols reactions of benzyl alcohols with cycloheptanones and acyclic ketones fail or give unsatisfactory results.